EXPLORING THE KEY FACTORS INFLUENCING YOUNG CONSUMERS' PURCHASING DECISIONS OF HALAL PRODUCTS IN EAST JAVA - Berto Mulia Wibawa; Rachma Rizqina Mardhotillah; Cepryana Sathalica Widyananda (Journal of Halal Research, Policy, and Industry, 2024)
This research explores the key factors influencing young consumers' purchasing decisions of halal products in East Java, with a focus on Generation Z. In an increasingly digital and globally connected world, young consumers are more aware of halal principles and how they align with religious, ethical, and social values. The study investigates how various factors—such as attitude toward halal, trust in halal certification, and the role of digital marketing—impact purchasing decisions. Using a quantitative approach, data was collected through surveys distributed to Gen Z consumers in East Java. The results reveal that attitude toward halal is a significant predictor of purchasing behavior, with trust in halal certification further strengthening the decision-making process. Additionally, digital marketing efforts play a crucial role in shaping consumer awareness and confidence in halal products. This study concludes that a combination of religious adherence, trust, and effective digital engagement strategies strongly influences the purchasing decisions of young consumers in East Java. The findings provide valuable insights for marketers and businesses aiming to target the growing halal market among younger demographics.